Impact of Delafloxacin (DLX) and Vancomycin/Aztreonam (VAN/AZ) on Resolution of Signs and Symptoms of Acute Bacterial Skin and Skin Structure Infections (ABSSSI). (4th October 2017) - Giordano, Philip; Pullman, John; Lawrence, Laura; Quintas, Megan; Tseng, Carol; Cammarata, Sue K
Abstract: Background: Delafloxacin (DLX), an anionic fluoroquinolone antibiotic with Gram-negative and Gram-positive activity including MRSA, is in development for treatment of ABSSSI. In a global phase 3 ABSSSI trial, DLX was non-inferior to VAN/AZ in both objective and clinical response endpoints. Clinical signs and symptoms (S&S) and lesion size measurements also were evaluated in this trial Methods: A multicenter, double-blind trial of adults with ABSSSI randomized patients 1:1 to receive either DLX monotherapy 300mg q12h IV or VAN 15 mg/kg (actual body weight) with AZ for 5 – 14 days. Aztreonam was discontinued once Gram-negative infection was excluded in the VAN arm. The presence or absence of S&S were collected at each evaluation point. Patients with complete resolution of clinical S&S were classified as complete cures. Lesions were measured by digital planimetry. Patient-reported pain was recorded by numerical rating scale (NRS; 0=no pain, 10=worst pain). Assessments were completed at baseline, during and at end of treatment (EOT), at Follow-up (FU day 14) and Late Follow-up (LFU day 21–28). Results: 660 patients were randomized in US, Europe, and Israel. 63% were male with mean age 46 yrs. 39% had cellulitis, 25% abscesses, 35% wound and 1% burn infections. Baseline erythema and induration were seen in 100% and 98% of patients, respectively. Mean area of erythema and induration at baseline was 307 and 107 cm 2 respectively. Most common locations for lesions were lower (40%) and upper extremities (34 %). S. aureus was the most common isolate. Mean days of treatment was 6 days in either group. DLX and VAN/AZ patients had comparable impact on S&S with complete resolution in 27% vs. 24 % at EOT, and 52% vs. 51% at FU, and 70% vs. 67% at LFU for DLX vs. VAN/AZ, respectively. DLX was comparable to VAN/AZ in percent reduction in erythema over time (figure). There was a median reduction of 58% vs. 59% at 48–72 hours, 94% vs. 94% at EOT, and 100% vs. 100% at LFU for DLX and VAN/AZ respectively. Baseline mean pain scores were 8/10 with scores of 2.5/10 at EOT and 1/10 at FU for both treatment groups. Conclusion: Treatment with DLX and VAN/AZ provided rapid improvement in clinical signs and symptoms in ABSSSI with comparable reductions in S&S, lesion size and pain score. Disclosures: P. Giordano, Melinta: Investigator, Research grant; J. Pullman, Melinta: Investigator, Research grant; L. Lawrence, Melinta: Employee, Salary; M. Quintas, Melinta: Employee, Salary; C. Tseng, Melinta: Consultant and Research Contractor, Consulting fee; S. K. Cammarata, Melinta Therapeutics: Employee, Salary